Work Absenteeism and Its Determinant Factors in Patients with Ankylosing Spondylitis: A Cross-Sectional Study - Julide ÖNCÜ; Fatma BAŞOĞLU; Banu KURAN (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate work absenteeism and its determinant factors in patients with ankylosing spondylitis (AS). Patients and methods: A total of 88 patients were referred to our outpatient clinic with a definitive diagnosis of AS. Of these, the 46 full-time workers (9 women; 37 men; mean age 38.7±8.5 years; range 16 to 60 years) were evaluated. The impact of disease-related factors on absenteeism were analyzed via the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Function Index (BASFI), and the Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire. The disease duration and morning stiffness as well as factors such as job-related physical duties [heavy lifting (>10 kg), working with the trunk in an awkward posture, prolonged sitting and standing while working, driving a vehicle for >6 hrs/day], type of occupation, duration of work (years), average hours worked per week, and psychosocial risk factors (job-related distress, fear of returning to work, and job satisfaction) were also assessed. Results: The mean disease duration was 8±7 years, and the mean days of work absenteeism were 44.8±10.1. There was a significant correlation between work absenteeism and the BASDAI, BASFI, ASQoL, and morning stiffness scores. Among the job-related physical duties and psychosocial risk factors, heavy lifting, job-related distress, fear of returning to work, and job satisfaction were associated with most days of absenteeism. In a stepwise logistic regression analysis, the only items that were significantly related to absenteeism were the high BASDAI scores and low job satisfaction. None of the other demographic characteristics or physical factors demonstrated significance. Conclusion: Our study results showed that work absenteeism is an important outcome of AS, with the most important determinant factors being the BASDAI scores and the level of job satisfaction.